การศึกษาและการเสริมสร้างคุณลักษณะพรหมวิหาร 4 ของนิสิตหลักสูตรการศึกษาบัณฑิต (กศ.บ.) 5 ปี มหาวิทยาลัยศรีนครินทรวิโรฒ - แสนอุบล ครรชิต; ครามานนท์ สิทธิพร; คัมภิรานนท์ อสมา (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2020)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์1) เพื่อศึกษาระดับคุณลักษณะพรหมวิหาร 4 ของนิสิต 2) เพื่อเปรียบเทียบคุณลักษณะพรหมวิหาร 4 ของนิสิตกลุ่มทดลอง ก่อนและหลังการเสริมสร้างโดยกลุ่มพัฒนาตนและการปรึกษาเชิงจิตวิทยาแนวพุทธ และ 3) เพื่อเปรียบเทียบคุณลักษณะพรหมวิหาร 4 ระหว่างนิสิตกลุ่มทดลองและนิสิตกลุ่มควบคุม ประชากรที่ใช้ในการศึกษาระดับคุณลักษณะพรหมวิหาร 4 เป็นนิสิตหลักสูตรการศึกษาบัณฑิต (กศ.บ.) 5 ปี ชั้นปีที่ 2 มหาวิทยาลัยศรีนครินทรวิโรฒ จำนวน 403 คน ส่วนกลุ่มตัวอย่างที่ใช้ในการเสริมสร้างคุณลักษณะพรหมวิหาร 4 โดยกลุ่มพัฒนาตนและการปรึกษาเชิงจิตวิทยาแนวพุทธเป็นนิสิตหลักสูตรการศึกษาบัณฑิต (กศ.บ.) 5 ปี ชั้นปีที่ 2 จำนวน 12 คนที่เลือกแบบเจาะจง (purposive sampling) จากนิสิตที่มีค่าเฉลี่ยคุณลักษณะพรหมวิหาร 4 ต่ำกว่าเปอร์เซ็นต์ไทล์ที่ 25 ลงมา และมีความสมัครใจในการเข้าร่วมวิจัย แล้วสุ่มอย่างง่ายเป็นกลุ่มทดลองและกลุ่มควบคุมกลุ่มละ 6 คน โดย เครื่องมือที่ใช้ในการวิจัย คือ แบบวัดคุณลักษณะพรหมวิหาร 4 ที่มีค่าอำนาจจำแนกอยู่ระหว่าง 0.21-0.66 มีความเชื่อมั่นเท่ากับ 0.86 และโปรแกรมกลุ่มพัฒนาตนและการปรึกษาเชิงจิตวิทยาแนวพุทธมีค่าความเที่ยงตรงเชิงเนื้อหาเท่ากับ 1.00 สถิติที่ใช้ในการวิเคราะห์ข้อมูล ประกอบด้วย ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตราฐาน การเปรียบเทียบความแตกต่างของค่าเฉลี่ยในกลุ่มที่ไม่เป็นอิสระจากกัน และการเปรียบเทียบความแตกต่างของค่าเฉลี่ยแบบเป็นอิสระจากกัน ผลการวิจัยพบว่า 1) นิสิตมีค่าเฉลี่ยพรหมวิหาร 4 อยู่ในระดับมาก (M=4.08) และเมื่อพิจารณาเป็นรายด้าน พบว่า มุทิตามีค่าเฉลี่ยสูงสุด (M=4.21)รองลงมาคือ เมตตาและกรุณา (M=4.07) และอุเบกขา(M=3.95) ตามลำดับ 2) หลังการเสริมสร้างโดยกลุ่มพัฒนาตนและการปรึกษาเชิงจิตวิทยาแนวพุทธ นิสิตกลุ่มทดลองมีค่าเฉลี่ยคุณลักษณะพรหมวิหาร 4 โดยรวม และด้านเมตตาและด้านกรุณาเพิ่มสูงขึ้นอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และ 3) หลังการเสริมสร้างโดยกลุ่มพัฒนาตนและการปรึกษาเชิงจิตวิทยาแนวพุทธนิสิตกลุ่มทดลองมีค่าเฉลี่ยด้านกรุณาที่สูงขึ้นกว่านิสิตกลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ABSTRACT The purposes of this research were 1) to study rank of four Brahamavihara characters of undergraduate students in 5years teacher program at Srinakharinwirot University 2) to comparison of four Brahamavihara characters of undergraduate students in 5 years teacher program at Srinakharinwirot University of experiment before and after through Personal growth and Buddhism Counseling Group (PBCG) and 3) to comparison of four Brahamavihara characters of undergraduate students in 5 years teacher program at Srinakharinwirot University between experiment group and control group. The samples in this study were four hundred three of undergraduate students in 5 years teacher program at Srinakharinwirot University and the sample in this experiment were twelve at four Brahamavihara characters of undergraduate students in 5 years teacher program at Srinakharinwirot University divide six experiment group and control group selected by purposive sampling through Personal growth and Buddhism Counseling Group mean at the twenty-fifth percentile and lower in order to voluntarily to participate in the experiment. The research instruments used in this study were four Brahamavihara characters scale with discrimination ranging from 0.21 to 0.66 and the reliability coefficient of 0.86 and Personal growth and Buddhism Counseling Group program with an index of item-objective congruence score of 1.00. The statistical analyses employed were descriptive statistics t-test for dependent samples and t-test for independent samples. The research results were as follows: 1) The four Brahamavihara characters of undergraduate students with adolescentswere at a high level (M=4.08). The factor of each, in descending order as follows:merciful (M=4.21) kindness and feelings of pleasure (M=4.21) and detach (M=3.95) 2) After Personal growth and Buddhism Counseling Group of undergraduate students experiment group were mean of four Brahamavihara characters and the factor of each, in descending order as follow: merciful and kindness and increased at a .01 level and 3)after Personal growth and Buddhism Counseling Group of undergraduate students experiment group were mean of kindness than undergraduate students control group and increased at a .05 level. Keywords: Four Brahamavihara Characters, Personal growth and Buddhism Counseling Gro